2007
DOI: 10.1590/s0100-83582007000300008
|View full text |Cite
|
Sign up to set email alerts
|

Problemática da ocorrência de diferentes espécies de capim-colchão (Digitaria spp.) na cultura da cana-de-açúcar

Abstract: RESUMO -O gênero Digitaria inclui cerca de 300 espécies de plantas, distribuídas em regiões tropicais e subtropicais de ambos os hemisférios. No Estado de São Paulo, esse gênero contém 13 espécies descritas, nas quais a diferenciação visual torna-se difícil de ser feita no campo, devido à grande semelhança morfológica entre elas. As espécies Digitaria nuda, D. ciliaris, D. horizontalis e D. bicornis, conhecidas popularmente por capim-colchão, são plantas daninhas comumente encontradas em áreas de produção de c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
12

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 11 publications
(12 reference statements)
1
12
0
12
Order By: Relevance
“…ha -1 , which provided an efficient control of the access of D. nuda, averaged at 90% after 7 DAA and 100% after 14 DAA. In a study on the herbicides efficacy, controlling the species Digitaria spp., Dias et al (2007) found that the herbicides from the chemical groups of triazines (ametrine) and isoxazolines (isoxaflutole) also have excellent levels of control.…”
Section: Resultsmentioning
confidence: 99%
“…ha -1 , which provided an efficient control of the access of D. nuda, averaged at 90% after 7 DAA and 100% after 14 DAA. In a study on the herbicides efficacy, controlling the species Digitaria spp., Dias et al (2007) found that the herbicides from the chemical groups of triazines (ametrine) and isoxazolines (isoxaflutole) also have excellent levels of control.…”
Section: Resultsmentioning
confidence: 99%
“…*SDT1 (semeadura direta sem adubação e com herbicida); SDT2 (semeadura direta com adubação mineral e herbicida); SDT3 (semeadura direta com composto orgânico e herbicida) e SDO (semeadura direta com composto orgânico e roçada) Dias et al (2007), a tolerância de certas espécies de plantas daninhas a herbicidas é resultado da capacidade inata da espécie em suportar aplicações de herbicidas nas doses recomendadas, sem alterações marcantes em seu crescimento e/ou desenvolvimento.…”
Section: Methodsunclassified
“…They are plants belonging to the botanical family Poaceae (Gramineae), subfamily of Panicoidaea, the Paniceae tribe, with fairly wide distribution in Brazil, present in the Northeast, Midwest, Southeast and South (Canto-Dorow, 2001;Dias et al, 2007). These species of crabgrass are highly aggressive and reported as being a problem in 60 countries, infesting more than 30 economically important crops.…”
Section: Introductionmentioning
confidence: 99%
“…Among the observed proportions in the complex D. nuda has dominated communities in which it was previously considered rare (Dias et al, 2007). One reason for this change in the dynamics of the Digitaria species is the continuous application, for several years, of herbicides inhibiting photosystem II (PSII) and/or herbicides of the imidazolinone chemical group (inhibitors of acetolactate synthase (ALS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation